Contest for Attention in a Quality-Ladder Model of Endogenous Growth - Volker Grossmann (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper develops a quality-ladder model of endogenous growth to study the interplay between in-house R&D and marketing expenditure. Although promotional activity is modelled as purely wasteful competition among firms for attention, it unambiguously fosters innovation activity of firms, and possibly, leads to faster growth. This result rests on two premises which are consistent with empirical evidence. First, if firms incur higher sunk costs for marketing, concentration and firm sizes rise. Second, firm size and R&D expenditure are positively related. As a result, R&D investments per firm may even become excessive, whereas being inefficiently low in the benchmark case without marketing. This has non-trivial consequences for the socially optimal policy design with respect to R&D subsidies and entry incentives.
Keywords: 330; contest for attention; endogenous growth; innovation activity; marketing; R&D subsidies; scale effects